2011
DOI: 10.1007/s11248-011-9564-0
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of rat embryonic stem cells and generation of protease-activated receptor-2 knockout rats

Abstract: One of the remarkable achievements in knockout (KO) rat production reported during the period 2008-2010 is the derivation of authentic embryonic stem (ES) cells from rat blastocysts using a novel culture medium containing glycogen synthase kinase 3 and mitogen-activated protein kinase kinase inhibitors (2i medium). Here, we report gene-targeting technology via homologous recombination in rat ES cells, demonstrating its use through production of a protease-activated receptor-2 gene (Par-2) KO rat. We began by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Thus, precise gene targeting technologies would allow many important biomedical questions to be addressed. Despite the recent derivation of rat ES cells (Buehr et al 2008;Li et al 2008) to generate knockout (Tong et al 2010;Yamamoto et al 2012) and knock-in rats (Meek et al 2010), rat ES cells are still less robust than mouse ES cells (Zheng et al 2012). The emergence of engineered nucleases, allowing the rapid and effective generation of genetically modified animals, opens the door to gene targeting in rat but also in other species for which ES cells are not yet available, and provides a faster and more cost-effective strategy compared to the use of ES cells.…”
mentioning
confidence: 99%
“…Thus, precise gene targeting technologies would allow many important biomedical questions to be addressed. Despite the recent derivation of rat ES cells (Buehr et al 2008;Li et al 2008) to generate knockout (Tong et al 2010;Yamamoto et al 2012) and knock-in rats (Meek et al 2010), rat ES cells are still less robust than mouse ES cells (Zheng et al 2012). The emergence of engineered nucleases, allowing the rapid and effective generation of genetically modified animals, opens the door to gene targeting in rat but also in other species for which ES cells are not yet available, and provides a faster and more cost-effective strategy compared to the use of ES cells.…”
mentioning
confidence: 99%
“…Although germline‐competent rat ES cells have been derived from various strains 1, 2, 23, 35, the knockout rats generated via homologous recombination have only been achieved in DA rats 27, 32, 34. It has also been reported that the gene targeting event resulted in the failure of germline transmission in SD rat ES cells 32.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previously published rat knockout work in ES cells 27, 32, 34, our gene targeting procedure is optimized in multiple steps, including β2 mouse feeders, positive neomycin ( neo ) and negative FIAU ( tk ) selections, 3i culture medium, DA/SD hybrid recipient blastocysts, and so on. These resulted in higher targeting efficiency and germline transmission efficiency than other procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, the production of genetically modified rats has been difficult due to problems in rat ESCs after gene introduction [52]. Gene-targeting technology via Advances in transgenic animals homologous recombination in rat ES cells demonstrated its use through production of a protease-activated receptor-2 gene (Par-2) KO rat [53]. Targeted disruption of myostatin (mstn) gene in yellow catfish was performed using engineered zinc-finger nucleases (ZFNs), and six mstn nju6/?…”
Section: Gene Targetingmentioning
confidence: 99%